Merging athletic training and nursing clinical education - Towne, Ben; Keith, Anne B. (Groupwork, 2012)
Combining nursing and athletic training clinical experiences can serve to better prepare the health care student for future team work with other disciplines and a diverse patient population. International service-learning courses can enhance the undergraduate student experience while also serving those most in need. Athletic Training and Nursing students at the University of Southern Maine blend together as an interdisciplinary group to participate in a community based health care initiative to rural citizens in the Dominican Republic. This unique experience assists students to better understand their role as global citizens, introduces cultural competency, and affords the student the opportunity to better identify both the background of the patients they treat, and the differing health care providers they work alongside. A review of literature suggests that incorporating both cultural competency and service learning into existing educational programs increases affective learning and personal development. Service-learning via groupwork benefits students, faculty and the communities involved, enabling students to gain insight into other populations and/or cultures with which they lack familiarity. There are both advantages and disadvantages to integrating cultural competency and service learning into undergraduate programs.